The Effectiveness of Small Discussion on Teaching Reading Comprehension in Narrative Text of Engilsh Education Department of STKIP Muhammadiyah Bogor - Srinawati, Wawat (UICELL, 2018)
The objectives of this research is to investigate whether there is significant difference between student’s reading comprehension before and after giving the treatment by using Small Group Discussion and to find out the result in narrative text. The sample of this research are the first semester at STKIP Muhammadiyah Bogor  in academic year 2018/2019. The students’ populations of first semester at STKIP Muhammadiyah Bogor are 60 students, and the samples are 30 students (30 students for experiment class and 30 students for controlled class). The writer used Normality test and T-test. For knowing Normality test, the calculation gained the score X2 statistic = 2,521; and from the table of chi kuadrat for α = 0,05 and dk=5 gained X t2able = 11,070. And for T-Test gained score ttable for α = 0,05 and dk 58 was 7,71. Because of tstatistic = 8,092 was bigger than ttable = 7,71 or tstatistic > ttable it means Ho was rejected and Ha was accepted. It means that there was effectiveness of Small Group Discussion on Teaching Reading Comprehension in Narrative Text of first at STKIP Muhammadiyah Bogor.